In vitro Antioxidant Potential of Standardized Ethanol Extract of Clerodendron serratum Linn. Leaves - Vazhayil, Babitha K.; Sundaram, R. Shanmuga; Patel, Deepika; Alex, A. Renjith; Gomathi, S.; Roy, Pinki; Kumar, R. Sambath (Asian Journal of Chemistry, 2016)
Leaves of Clerodendron serratum were investigated for their phytochemical constituents like phenolic compounds, flavonoids, tannins, terpenoids, steroids and screened for in vitro antioxidant activity against 2,2-diphenyl-2-picrylhydrazyl (DPPH), superoxide anion, hydroxyl radical, nitric oxide radical, total antioxidant capacity and reducing power. Estimation of total phenolic compounds by Folin-Ciocalteu reagent indicated that the extract (1 mg) contained 130 μg of gallic acid equivalents and that of total flavonoids demonstrated 7 μg of quercetin equivalents in 1mg of the extract. DPPH radical, hydroxyl radical, nitric oxide radical and superoxide radical scavenging activities were found to be 211, 138.35, 171.54 and 177.93 μg/mL, respectively. The extract showed significant activities in all antioxidant assays and the reducing power of the extract was found to be significantly higher than ascorbic acid. The results obtained indicate that in vitro antioxidant property of Clerodendron serratum leaf extract may be due to high content of phenolic compounds and justify the therapeutic applications of the plant in the indigenous and traditional system of medicine for the treatment of inflammatory and neurological disorders.